Effect of wash coat layers on the conversion efficiency of a catalytic converter in the SI engine. Issue 1 (31st December 2022) - Jeyakumar, Nagarajan; Arumugam, C. A. K.; Narayanasamy, Bose; Rajkumar, R.
Abstract : The present work deals with the effect of different wash coat layers such as micro alumina, nano alumina and yttria on the reduction of HC, CO emissions when compared to base line emissions. The morphology of various wash coat materials was characterised by means of a scanning electron microscope. The experimental investigations were carried out in a four-stroke spark ignition engine before and after ageing of catalytic converters. The decrease in HC and CO emissions was found to be in the order of nano alumina, yttria dual and micro alumina when compared to base line readings before ageing. The decreases in HC and CO emissions were found to be in the order of yttria dual, nano alumina and micro alumina when compared to base line readings after ageing. The maximum conversion of yttria dual can be attributed to the adhesion properties of the wash coat with the substrate.